Characterising dark net marketplace purchasers in a sample of regular psychostimulant users - Van Buskirk, J.; Roxburgh, A.; Bruno, R.; Naicker, S.; Lenton, Simon; Sutherland, R.; Whittaker, E.; Sindicich, N.; Matthews, A.; Butler, K.; Burns, L. (2016)
Background: The past five years has seen a proliferation in marketplaces operating on the 'dark net' selling licit and illicit substances. While monitoring systems have investigated the specific substances for sale on these marketplaces, less is known about consumer motivations for accessing these marketplaces and factors associated with their use. Methods: An Australian national sample (n = 800) recruited on the basis of regular psychostimulant use was recruited and asked about purchasing substances from dark net marketplaces and the reasons for doing so. Respondents who had purchased any drug from a dark net marketplace in the preceding year were compared to those who had not in terms of demographic information and factors including drug use, criminal activity, and sexual and mental health. Results: Nine percent (n = 68) of the sample had purchased from dark net markets in the past year. MDMA, LSD and cannabis were the three most commonly purchased substances, and the main benefits cited for purchasing online were the better quality and lower cost of drugs available. Controlling for other factors, participants who purchased from dark net marketplaces in the past year tended to be younger, more likely to be involved in recent property crime and to have used more classes of drugs in the preceding six months, specifically psychedelics and 'new psychoactive drugs'. Conclusions: Though a small minority of participants reported having purchased drugs online in the preceding six months, these appeared to be a more.